Reliability and validity of the DBT-VLCS: A measure to code validation strategies in dialectical behavior therapy sessions. (3rd May 2016) - Carson-Wong, Amanda; Rizvi, Shireen
Abstract: Objective: There are six strategies or validation levels in dialectical behavior therapy (DBT), yet there are no measures designed to code for them. This absence limits our understanding of the relationship between validation strategies and treatment outcome. The DBT-Validation Level Coding Scale (DBT-VLCS) was developed to overcome this limitation.Method: This research reports on the interrater reliability and content validity for the DBT-VLCS.Results: Overall, interrater reliability was excellent for all items, with the exception of two items that demonstrated good reliability. Good content validity was demonstrated for six of the seven items.Conclusions: This preliminary study suggests that the DBT-VLCS is a reliable and valid measure to code the presence of validation in DBT. This measure creates the opportunity for research that has not previously been possible.